Optimizing Document Retrieval by Measurement Resemblance Between Semantic Word Methods - Ratchatawetchakul, Kamonwan; Sarnthong, Apichai; Ratchatawetchakul, Weerayut; Ratchatawetchakul, Yongyut (Journal of Applied Informatics and Technology, 2020)
The aims of article to present the method for measuring semantic similarity between words. Data test are documents in the computer domain from ThaiLIS : Thai Library Integration System 50 documents and prepare a Dublin Core metadata for documentation such as Title, Keyword / Subject, Description / Abstract and Source. Create ontology on Web Ontology Language (OWL) by the word form https://technology.in.th/thesaurus about 402 words that is thesaurus website by National Science and Technology Development Agency. This research use Dijkstra algorithm for shorted part between node to node relate by Edge and Node such as skos:prefLabel , skos:broader, skos:narrower, skos:related and skos:altLabel. The results showed that method of measuring semantic similarity between words by shortest path method proposed by the researcher shows efficiency more than cosine similarity, accuracy of retrieval with F-measure and MRR. Cosine Similarity measurement and the results of the retrieval meet users’ needs.